PENGARUH METODE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI SMA - sarwati, Sarwati (Cocos Bio, 2025)
The purpose of this research was to determine the impact of the Team Assisted Individualization (TAI) method on the learning outcomes of eleventh grade students at SMA NW Tebaban for the 2024/2025 academic year. This study employed a pre- experimental one-group pretest-posttest design. The population of this research comprised all eleventh-grade students at SMA NW Tebaban for the 2024/2025 academic year, totaling 23 students. The research design used was a pre-test – post- test with treatment administered over a certain period, measuring with tests before (pre-test) and after (post-test) the treatment, and modifying the pre-test and post-test scores obtained from the students’ test results after the intervention. Data analysis employed an independent sample t-test, supported by the Shapiro-Wilk test conducted by the researcher. The hypothesis results indicated that tcount > ttable (0.9857 > 4.28), meaning Ho was rejected and Ha was accepted. Thus, it can be concluded that there is an impact of the Team Assisted Individualization (TAI) method on the learning outcomes of eleventh grade students at SMA NW Tebaban for the 2024/2025 academic year.